2017
DOI: 10.1016/j.srhc.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Routine interventions in childbirth before and after initiation of an Action Research project

Abstract: Acknowledgements 2We acknowledge the contribution of the midwives who co-created the data through their action learning sets, and the Fyrbodal Research and Development Council Region Västra Götaland, Sweden for financial support of this research. AbstractBackground: Unnecessary routine interventions in uncomplicated labour and birth, like cardiotocography (CTG), amniotomy, use of scalp electrode and oxytocin treatment, are associated with further interventions that could harm the woman and the infant. A four y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…From all discussed above, we can see in this study that various medical interventions prevail in Chinese urban obstetric settings. In concordance with our findings, previous studies have also noted that there is a continually increasing trend in routine use of medico-technical interventions [17,45,46]. Lu et al also pointed out the current situation of frequently used intrapartum interventions which may substantially distort the labour pattern [47].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…From all discussed above, we can see in this study that various medical interventions prevail in Chinese urban obstetric settings. In concordance with our findings, previous studies have also noted that there is a continually increasing trend in routine use of medico-technical interventions [17,45,46]. Lu et al also pointed out the current situation of frequently used intrapartum interventions which may substantially distort the labour pattern [47].…”
Section: Discussionsupporting
confidence: 92%
“…Many common obstetric practices, however, are of limited or uncertain benefit for low-risk women in spontaneous labour [15]. Unnecessary routine interventions in labour are actually associated with further interventions and result in decreased rates of spontaneous vaginal birth [16,17]. Bohren et al reported that more than a third of women experienced mistreatment and were particularly vulnerable around the time of birth [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amniotomy is a commonly used labour intervention, worldwide, despite limited evidence on it shortening the length of labour ( Smyth et al., 2013 ). Besides the avoidable harm and increased need for other additional interventions, inappropriate use of interventions is costly for health systems ( Miller et al., 2016 ; Nyman et al., 2017 ). Further, medicalisation of birth can undermine women's capacity and affect the childbirth experience negatively ( Oladapo et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, an individualized treatment does not exist, and arrested labor is handled according to adopted clinical guidelines rather than taking into account the status of the uterus and the pathological and anatomical conditions of pregnant women [ 1 ]. Most of the randomized studies had a high rate of operative delivery in abnormal labor [ 10 ]. The present study compared all regimens of OXT available in the market for augmentation of labor in child birth, aiming to help obstetrics with the selection of proper regimens of OXT for augmentation of labor.…”
Section: Introductionmentioning
confidence: 99%